2002
DOI: 10.1002/j.1551-8833.2002.tb09474.x
|View full text |Cite
|
Sign up to set email alerts
|

DOC and DBP precursors in western US watersheds and reservoirs

Abstract: Horseshoe Reservoir, shown in this aerial view, is part of a reservoir system that is used as the primary raw drinking water supply for cities in the metropolitan Phoenix, Ariz., area.Regulations for disinfection by-products (DBPs) will be expensive to meet through modifications in water treatment technology alone. An adjunct DBP control strategy is to reduce concentrations of DBP precursors in source waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…3). These small, but statistically significant, changes could be due to photodegradation (Brooks et al, 2007;Kraus et al, 2011;Cory et al, 2014) coupled with autochthonous production of DOC (Chin et al, 1994;Nguyen et al, 2002). A similar decreasing SUVA 254 pattern from upstream to downstream of reservoirs was reported below Lake Powell and Lake Mead in the lower Colorado River basin (Miller, 2012).…”
supporting
confidence: 53%
“…3). These small, but statistically significant, changes could be due to photodegradation (Brooks et al, 2007;Kraus et al, 2011;Cory et al, 2014) coupled with autochthonous production of DOC (Chin et al, 1994;Nguyen et al, 2002). A similar decreasing SUVA 254 pattern from upstream to downstream of reservoirs was reported below Lake Powell and Lake Mead in the lower Colorado River basin (Miller, 2012).…”
supporting
confidence: 53%
“…Other factors that clearly will affect reservoir DOM cycling include temperature, solar radiation, and residence time (Nguyen et al 2002, Mash et al 2004. For example, longer water residence times during periods where respiration exceeds photosynthesis may provide an opportunity for environmental processing of DOM, which may reduce the DBP precursor pool (Jack et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, both STHMFP and SHAAFP were notably lower in May compared to January. Nguyen et al (2002) also reported losses of THM and HAA precursors during reservoir residence time. Similarly, the Ohio River was found to be a net sink for THM precursors due to the predominance of bacterial respiration over photosynthesis (Jack et al 2002).…”
Section: Summer (Jul-sep)mentioning
confidence: 91%
See 2 more Smart Citations